Environmental Sanitation as the Key Determinant of Stunting Incidence in Kertapati District - Rahmadita Zinda Haniifa; Fatmah; Rachmadhi Purwana (JURNAL KESEHATAN LINGKUNGAN, 2026)
Introduction: Stunting is a major public health problem in low- and middle-income countries due to its long-term impact on child growth along with their cognitive and emotional development over both the short and long term. In 2022, data showed that around 22.3% of children globally experienced stunting, underlining the severity of the issue, and even though Indonesia made some strides with the latest SSGI showing a drop to 19.8% in 2024, the figure is still above the national target of 14%. In Palembang City, reports 20.5% indicating a persistent local health issue. Availability of safe water, decent toilets, and better air in homes all influence this problem. In Kertapati District, people face issues with unsafe water inadequate sanitation and exposure to indoor smoke so this research aimed to identify the main factors behind stunting among children under five. Methods: A cross-sectional study involving 6,095 children under five and 178 respondents chosen through random sampling. Variables included access to safe drinking water, latrine ownership and household air pollution. Data collection used interviews and observations before being analyzed using SPSS 27. Results and Discussion: Only 26.4% of households had adequate environmental conditions. All variables were significantly associated with stunting, with household air pollution identified as the most dominant factor (OR = 10.268). Conclusion: Stunting in Kertapati District mostly linked to environmental sanitation and household air pollution. To cut stunting rates, have to start with improving water and sanitation.